2003
DOI: 10.5432/ijshs.1.207
|View full text |Cite
|
Sign up to set email alerts
|

Simple Assessment of Lactate Threshold by Means of the Bench Stepping in Older Population

Abstract: The purpose of this study was to develop a simple assessment of lactate threshold (LT) in older people. Two-hundreds and nine subjects, aged 65 to 90 years old, performed a bench stepping test by means of a 20 cm bench at 10 to 35 ascends per minute of the stepping rate. In 52 of 209 subjects, we determined the metabolic equivalents corresponding to exercise intensity of which lactate (LA) increased 0.1, 0.2, 0.3, 0.4, 0.5 and 1 mmol/l from baseline level, LA corresponding to the baseline level and 2 mmol/l (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…In order to solve these problems, we have proposed a simple assessment of LT that used METs@LAr+0.1 by means of LA obtained from 2 intensities. The accuracy of this assessment was 13.5% (%2SEE of LT) in older people [Ayabe et al, (2003)]. Additionally present investigation demonstrated that this simple assessment had similar accuracy in younger adults.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In order to solve these problems, we have proposed a simple assessment of LT that used METs@LAr+0.1 by means of LA obtained from 2 intensities. The accuracy of this assessment was 13.5% (%2SEE of LT) in older people [Ayabe et al, (2003)]. Additionally present investigation demonstrated that this simple assessment had similar accuracy in younger adults.…”
Section: Discussionsupporting
confidence: 57%
“…The graded exercise test used a submaximal graded step test, following the our previous investigation [Ayabe et al, (2003)]. Exercise intensity was decided according to the exercise habits and aerobic capacity individually.…”
Section: Graded Exercise Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Walking and jogging are appropriate forms of exercise, but rain or harsh conditions such as extreme heat or icy conditions in winter can make it difficult to go outside; therefore, we recommend the benchstep exercise. This activity can be performed while watching television or listening to music, and the intensity can be easily maintained at a constant level or pace 77,78) . Home-based bench-stepping training offers optimal benefits for the elderly both as an aerobic exercise and as an effective strengthener of lower extremity muscles, such as the quadriceps and psoas major muscle, the major sites of sarcopenia in older people.…”
Section: Practical Exercise Trainingmentioning
confidence: 99%